Experimental and theoretical validation studies of ASnO3 (A = Ba, Ca, Sr) nanofibres for bioactivity applications. (4th February 2023) - Madhavan, Bradha; Suvitha, A.; Steephen, Ananth
ASnO3 perovskites were synthesised as nanofibres and their structures reformed by appropriate substitution to yield superior perovskites. The barium (Ba), calcium (Ca) and strontium (Sr) stannate nanofibres were blended through electro spinning process. The as prepared ASnO3 (A = Ba, Ca, Sr) samples were calcined at 1000°C. In order to classify their structural and morphological properties, the stannate nano strands were characterised using X-ray diffraction (XRD), transmission electron microscopy (TEM) and Atomic Force Microscopy (AFM). The findings show that the nanofibres obtained are 200 nm that have undergone diameter changes at 700°C after annealing. The XRD analysis reveals that the nanofibres have a strongly crystalline single-phase structure. From the AFM images of fibres, it was evident that these perovskites have high surface roughness and the three-dimensional image conveys that the strands have uniform nature. In addition, in order to measure molecular descriptors as well as to survey atomic elements, absorption, distribution, metabolism, excretion and toxicity (ADMET) parameters, physicochemical calculations and bioactivity are calculated using Swiss ADME and ADMET indicators.